Identifying a Set of Key Paradata Indicators in Web Surveys Based on the Relationship with Response Quality, Respondent Characteristics and Survey Estimates - Vasja Vehovar; Nejc Berzelak; Gregor Čehovin (Survey Research Methods)
Web survey paradata refer to digital traces left by respondents in web surveys that provide valuable insights into the response process. This paper aimed to identify a minimal set of paradata indicators that can be used in a similar manner to sociodemographic variables, i.e. as general characteristics of respondents. The exhaustive literature review revealed that web survey paradata have predominantly been studied in relation to response quality and sometimes also in relation to respondent characteristics and survey estimates. In the empirical part of the paper, a comprehensive set of raw paradata for a typical web survey was collected (n = 3,458). Based on the literature, an initial set of 112 paradata indicators was identified and further reduced through subsequent steps. Finally, the potential paradata indicators were examined for their statistically significant relationship with 9 response quality indicators, 8 respondent characteristics (including Big Five personality dimensions) and 13 survey estimates (related to computers and internet). The result of this process was a set of 12 key paradata indicators that could serve as a starting point for the creation of standardised paradata indicators that could potentially augment web survey response data.